1995
DOI: 10.1093/clinids/21.1.210
|View full text |Cite
|
Sign up to set email alerts
|

Renal Aspergilloma Due to Aspergillus flavus

Abstract: Renal aspergillomas have been reported only rarely. We report a case of Aspergillus flavus colonization of the renal pelvis and upper ureter of a patient with concomitant urinary schistosomiasis. The diagnosis was based on the demonstration of characteristic hyphal elements on direct microscopy and isolation of the fungus in culture. The patient was successfully treated with liposomal amphotericin B. This case emphasizes the importance of direct microscopic examination of urine specimens for prompt diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…flavus has been reported as a cause of both native and prosthetic valve endocarditis, which is occasionally a manifestation of disseminated aspergillosis (Demaria et al, 2000;Rao & Saha, 2000;Irles et al, 2004). Occasional cases occur in patients with no overt risk factors (Kennedy et al, 1998;Khan et al, 1995). In postoperative Aspergillus endocarditis, A. flavus accounts for 11.2 % of cases (Pasqualotto & Denning, 2006).…”
Section: Endocarditis and Pericarditismentioning
confidence: 99%
See 1 more Smart Citation
“…flavus has been reported as a cause of both native and prosthetic valve endocarditis, which is occasionally a manifestation of disseminated aspergillosis (Demaria et al, 2000;Rao & Saha, 2000;Irles et al, 2004). Occasional cases occur in patients with no overt risk factors (Kennedy et al, 1998;Khan et al, 1995). In postoperative Aspergillus endocarditis, A. flavus accounts for 11.2 % of cases (Pasqualotto & Denning, 2006).…”
Section: Endocarditis and Pericarditismentioning
confidence: 99%
“…Urinary tract aspergillosis due to A. flavus is rare, with few cases reported (Khan et al, 1995;Perez-Arellano et al, 2001;Kueter et al, 2002). Usually a unilateral or bilateral fungal bezoar of the urinary pelvis is the presenting problem.…”
Section: Urinary Tract Infectionmentioning
confidence: 99%
“…Haq et al (2007) described a case of localized renal aspergillosis in diabetic patients, Washawasky et al (1975) and Godec et al (1989) reported few cases of renal aspergillosis, while 7 cases were reported in the present study. Urinary tract aspergillosis due to A. flavus is rare with few reported cases (Khan et al, 1995;Perez-Arellano et al, 2001 andKueter et al, 2002) as we isolated 5 cases of A. falvus in this study.…”
Section: Discussionmentioning
confidence: 70%
“…16,17 In the second, an immunodepressed status caused by several conditions such as malignant hemopathies, 18,19 transplants, 20,21 (including kidneys from donors, 22,23 ), AIDS, 24,25 and longstanding steroid therapy 26 has been also reported. 16,17 In the second, an immunodepressed status caused by several conditions such as malignant hemopathies, 18,19 transplants, 20,21 (including kidneys from donors, 22,23 ), AIDS, 24,25 and longstanding steroid therapy 26 has been also reported.…”
Section: Discussionmentioning
confidence: 99%